Inulin from Several Tubers Available in Indonesia and the Growth of Gut Microbiota - Crespo, Ivan; Arindra, Augusto; Lualdi, Jessica Tashia; Rimba, Phoebe Anadita; Putra, Agus Budiawan Naro; Rahardja, Ritchie (Indonesian Journal of Life Sciences, 2020)
Indonesia has many types of tubers, some of them are gembolo tuber (Dioscorea bulbifera), lesser yam (Dioscorea esculenta), yam bean (Pachyrhizus erosus), and dahlia tuber (Dahlia pinnata); which are the sources of prebiotics. The term of prebiotics has been used since 1995 to describe the non-digestible components in food that positively alter gut microbiota activity and exhibit beneficial properties to the human body. One of the prebiotics that can be found in tubers is inulin. This review was aimed to compare inulin content in the above-mentioned tubers and their roles towards the growth of gut microbiota. Library searches using Semantic Scholar database was done. Findings showed that gembolo tuber contains the highest inulin content, followed by lesser yam, dahlia tuber, and yam bean. Moreover, inulin increases the population of Lactobacillus, Bifidobacterium, and Bacteroides while inhibits the growth of Escherichia coli and reduce the growth of Clostridium.